2018
DOI: 10.15835/nbha47111402
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Phytochemical, Antioxidant, Antibacterial and Anticancer Activity of Prunus domestica Fruit

Abstract: Plants have been used long ago through man history of life for their use in food and medicinal drives. In modern life, natural products have been extracted and isolated from several kinds of plants for the development of new drugs. There are numerous interests in natural antioxidants extracted from medicinal plants, vegetables and fruits, which might help to prevent oxidative damage. One of such plants is plum Prunus domestica L., family Rosaceae. Samples from ‘African Rose’, and ‘Santa Rosa’ plum cultivars we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
(42 reference statements)
4
15
1
Order By: Relevance
“…When comparing with literature reports, our results show a larger number of compounds than those reported for whole plum fruits from Egypt, USA, Serbia and Romania [16,[28][29][30] in flavan-3-ols and HCA, as well as similar results in flavonoids to those found for Egyptian cultivars [29]. Within studies focused on plum skins, our results show a greater number of compounds than cultivars from the USA and Germany [7,31].…”
Section: Flavan-3-ols Derivativessupporting
confidence: 81%
“…When comparing with literature reports, our results show a larger number of compounds than those reported for whole plum fruits from Egypt, USA, Serbia and Romania [16,[28][29][30] in flavan-3-ols and HCA, as well as similar results in flavonoids to those found for Egyptian cultivars [29]. Within studies focused on plum skins, our results show a greater number of compounds than cultivars from the USA and Germany [7,31].…”
Section: Flavan-3-ols Derivativessupporting
confidence: 81%
“…Saraswathi et al (2020) also recorded the antibacterial effect of Prunus cerasifera extracts showed antibacterial effect against Staphylococcus aureus, Bacillus subtilis, Proteus vulgaris, and Escherichia coli. In a similar study, the antibacterial activity of Prunus domestica fruits was found positive on both Gr (+) and Gr (-) bacteria (El-Beltagi et al, 2019). In another report, the antibacterial effect of dry and fresh plum extracts showed antibacterial effect against Staphylococcus aureus and Escherichia coli (Belhadj and Marzouki, 2014).…”
Section: Resultsmentioning
confidence: 72%
“…Several studies have revealed a direct relationship between the antioxidant activity and phenolic content on several date fruits (Allaith, 2008). Antioxidants in date fruits may save the body from many degenerative disorders by reducing oxidative stress owing to; (a) the phenolic compounds that suppresses nucleic acids, proteins and lipids oxidative damage (El-Beltagi, El-Ansary, Mostafa, Kamel, & Safwat, 2019b;El-Beltagi, Mohamed, Elmelegy, Eldesoky, & Safwat, 2019a;Nasir et al, 2015) and (b) activating of both enzymatic and non-enzymatic antioxidant systems (Borochov-Neori et al, 2015). Dates are classified by their moisture content, more than 30% of the soft date consists of moisture.…”
Section: Introductionmentioning
confidence: 99%